Epistolaria grodzieńsko-wileńskie. Nieznane listy Elizy Orzeszkowej do Emmy Jeleńskiej-Dmochowskiej - Kościewicz, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article presents an analysis of and editorial work on Eliza Orzeszkowa’s two unknown letters dated 1906, addressed to Emma Jeleńska-Dmochowska, discovered at the Lithuanian State Historical Archive in Vilnius (LVIA). What makes this correspondence so valuable is their author and their date of origin. In the former territories of the First Polish Republic incorporated by the Russian Empire, 1906 brought a temporary breath of freedom after decades of repression and lack of basic civil liberties. Hitherto unknown letters illuminate this socially- and politically-interesting period also in the biographies of the two key Polish writers living in the former Grand Duchy of Lithuania at the turn of the twentieth century. The letters are valuable for one more reason: they encourage us to take a closer look at the epistolary legacy of Emma Jeleńska-Dmochowska who was an outstanding personality in the literary and social life of modernist Vilnius, the creator of illegal Polish education in the Vilnius region and, finally, a writer and editor establishing numerous contacts with representatives of the Polish intellectual elite from the three partitions of Poland.